Spatial linkage and integrated driving pathways of high-quality rural e-commerce development in the context of digital villages in China - Fei, Liu; Bo, Wen; Xue, Wang; Yanan, Wang; Xiaoxi, Wang; Dan, Shang; Liang, Hou; Donghui, Zhang (Frontiers in Sustainable Food Systems, 2025)
This study investigates the high-quality development of rural e-commerce in China, focusing on its role in bridging the urban-rural divide and supporting rural revitalization in the context of digital village initiatives. Using data from 31 provinces (2018–2022), we assess the development levels, spatial linkages, and key drivers of rural e-commerce. Employing a combination of game-theoretic weighting, a modified gravity model, social network analysis, and fuzzy-set qualitative comparative analysis (fsQCA), the study identifies significant regional disparities in e-commerce development. Key drivers include infrastructure, technology, and policy, with central provinces such as Henan and Shandong playing pivotal roles, while peripheral regions face challenges due to lower digital integration. The study highlights two primary pathways for development: one driven by infrastructure and productivity improvements, and the other by technological innovation. These findings offer policy recommendations for enhancing regional collaboration and reducing the urban-rural divide through targeted investments in infrastructure and digital integration.